Pandangan Majelis Permusyawaratan Ulama Aceh Terhadap Sertifikasi Halal Produk Home Industry di Kota Banda Aceh - Faiyadh Musaddaq (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study aims to examine the role of MPU Aceh on halal certification of home industry products circulating in Banda Aceh City. In today's modern era, businesses in the field of production of ready-to-eat foods and beverages with a variety of flavors, forms, and claims avail successful in production. The availability of these various foods makes it easy for people to get it. However, on the other hand halal food products can be questioned. Guarantee halal of a food product can be realized among them in the form of halal certificate that accompanies a food product. The legal guarantor institution is the authority of the Indonesian Ulema Council (MUI) through LPPOM MUI, but in Aceh is authorized to handle the halal product of the Majelis Permusyawaratan Ulama (MPU) through the LPPOM MPU as stipulated in Qanun Aceh no. 8 of 2016 on the Product Warranty System. This type of research is field research / empirical (field research) and using qualitative descriptive approach. The primary data in this study comes from interviews with the Secretary of LPPOM Aceh and secondary data derived from related literature. Based on the data analysis, the researcher concludes that LPPOM Aceh has socialized the importance of halalness of a food product, but not maximally due to the point of view and attitude of market participants in Aceh, whether it is producers or consumers who tend apatis and a priori with halal labelisasi on any product They are consumption.